The information literacy and library PUC-Campinas graduation: an analysis of the 2008. (Perspectivas em Ciência da Informação, 2009)
This research sought to identify the contribuition of the Course of Library Science of Puc Campinas in the development of competence in information checking the skill's level in trainees and newcomers exposing the scenery os this competence and checking the aplication of this skill in their works. The survey was obtained from a questionnaire. The results were compared with campello and Abreu's research (2005) and the model proposed by Kuhlthau (1996), showing significant improvement in the subject's ambit.